Jejunal inflammatory fibroid polyp: a rare cause of intussusception (Ibrahim Medical College Journal, 2016)
Inflammatory fibroid polyp is a benign and non-neoplastic condition of the gastro-intestinal tract, commonly affecting the gastric antrum, though it can affect any part of the gastro-intestinal tract. It is a submucosal, sessile, polypoid mass composed of myofbroblast like mesenchymal cells, numerous small blood vessels and marked inflammatory cell infiltrate mainly eosinophils. It commonly presents with intestinal obstruction or intussusception. We present here a case of recurrent episodes of small intestinal sub-acute obstruction due to intermittent intussusception associated with inflammatory ûbroid polyp of jejunum.Ibrahim Med. Coll. J. 2015; 9(2): 58-60